ADAPTIVE HUMAN RESOURCE MANAGEMENT IN CONFRONTATION OF GLOBALIZATION'S CHALLENGES - Abdurrahman Sadikin; Hefri Yodiansyah; Yanti Budiasih; Sugiarti Sugiarti; Iwan Henri Kusnadi (SEAN Institute, 2023)
Globalization has created a dynamic and complex business environment, requiring organizations to adjust to unpredictable and rapid change. In this context, adaptive HR management is essential for sustaining the success and competitiveness of the organization. The method of research employed is a literature review, which entails gathering and analyzing literature on adaptive HR management and the challenges of globalization. The research findings indicate that adaptive human resource management necessitates the use of change-responsive strategies and practices, such as in recruitment, employee development, performance management, diversity management, technology use, effective leadership, and adaptive change management. This study highlights the advantages of adaptive human resource management, including increased employee productivity, workforce quality, organizational adaptability in the face of change, greater employee satisfaction, and competitive advantage. The practical implication of this study is the significance of organizations implementing adaptive HR strategies and practices in response to globalization's challenges.